2009
DOI: 10.1007/s00125-009-1522-5
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-mediated cortical activity in the slow frequency range is diminished in obese mice and promotes physical inactivity

Abstract: Aims/hypothesis There is evidence from mouse models and humans that alterations in insulin action in the brain are accompanied by an obese phenotype; however, the impact of insulin with regard to behavioural aspects such as locomotion is unknown. Methods To address insulin action in the brain with regard to cortical activity in distinct frequency bands and the behavioural consequences, the insulin signalling pathway was followed from the receptor to electrical activity and locomotion. Western blot analysis, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 36 publications
8
54
0
Order By: Relevance
“…The mean intakes of carbohydrate, saturated fatty acids and fat were adjusted for baseline, sex and age especially in the theta band, may interfere with physical activity during a lifestyle intervention that causes increased energy expenditure and subsequent loss of body fat. This is well in line with a recent study in mice showing an increase in locomotor activity after intracerebroventricular injection of insulin accompanied by increases in cortical theta and delta activity [12]. High insulin sensitivity of the brain at baseline was associated with lower intake of fat, especially saturated fat, during the lifestyle intervention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean intakes of carbohydrate, saturated fatty acids and fat were adjusted for baseline, sex and age especially in the theta band, may interfere with physical activity during a lifestyle intervention that causes increased energy expenditure and subsequent loss of body fat. This is well in line with a recent study in mice showing an increase in locomotor activity after intracerebroventricular injection of insulin accompanied by increases in cortical theta and delta activity [12]. High insulin sensitivity of the brain at baseline was associated with lower intake of fat, especially saturated fat, during the lifestyle intervention.…”
Section: Discussionsupporting
confidence: 91%
“…At that time, we speculated that fatty acids derived from visceral fat depots may cause insulin resistance of the brain and therefore lead to further weight gain. Indeed, recent studies confirmed that intracerebroventricular palmitic acid infusion and high-fat diet induce insulin resistance in different brain regions in mice and rats [12,14,15]. These observations, together with the present finding of high insulin sensitivity in the brain associated with lower intake of saturated fat, may suggest that insulin resistance in the brain elevates serum concentrations of saturated fatty acids not only by increasing visceral fat mass, but also more directly by decreasing physical activity and increasing intake of saturated fat.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, similar changes were not observed in epididymal or subcutaneous fat (Supplementary information, Figure S1F-S1G). A previous research has suggested that a reduction in physical activity occurs in mouse models of obesity [7]. Remarkably, BAT transplantation significantly reversed the reduction in physical activity in HFD-fed mice (Supplementary information, Figure S1C).…”
mentioning
confidence: 53%
“…In relation to hormones, insulin and leptin emerge as potential modulators of SPA. Hennige et al 53 showed that insulin i.c.v. injection promotes SPA in lean but not in diet-induced obese mice, which develop hypothalamic resistance to insulin 53 .…”
Section: Central Regulation Of Spontaneous Physical Activitymentioning
confidence: 99%